Pemanfaatan Teknologi Informasi di Perpustakaan Pengadilan Tinggi Padang - Zelpida, Zelpida; Desriyeni, Desriyeni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2015)
This article aims to describe: (1) use of information technology in Perpustakaan Pengadilan Tinggi Padang; (2) the obstacles encountered in the utilization of information technology in Pengadilan Tinggi Padang library; and (3) the efforts made in the utilization of information technology in Pengadilan Tinggi Padang library. Data were collected through direct observation and interviews with librarians at the Library of Pengadilan Tinggi Padang library. Analyzing data descriptively. By analyzing the data, we can conclude the following: First, the use of information technology in Pengadilan Tinggi Padanglibrary has not gone well. Secondly, the obstacles encountered in the utilization of information technology in Pengadilan Tinggi Padang library are: (1) the lack of power that truly skilled in the art; (2) the lack of specific training; (3) lack of funds or a special budget for the library; (4) the lack of facilities and infrastructure to support activities carried out in the library. Third, efforts made in the utilization of information technology in Pengadilan Tinggi Padanglibrary are (1) providing power truly skilled in the art; (2) provide training to librarians; (3) provide funds or special angggaran for the library; (4) provide the facilities and infrastructure needed in the management of the library. Keywords: utilization, technology, information.